Spatial Analysis of Human Health Risk Associated with Trihalomethanes in Drinking Water: A Case Study of Karachi, Pakistan - Zahida Karim; Bilal Aslam Qureshi; Ishtiaq Ghouri (Journal of Chemistry)
The objective of this study was to spatially analyze total trihalomethanes (TTHMs) and health risk associated with TTHMs in drinking water of different densely populated towns of Karachi city. Lifetime cancer risk and hazard index of THMs through oral ingestion and dermal absorption were calculated and mapped using kriging as an interpolation method to evaluate the carcinogenic and noncarcinogenic risk to human health in the study area. Lifetime cancer risk value due to the oral ingestion of TTHMs in different towns of the city was exceeded from 1.0×10−6, showing that residents of these towns were expected to be at higher cancer risk. The hazard index for different towns was found to be lower than unity, indicating that no adverse health effects are expected as a result of exposure to THMs.